Descriptive Analysis in Terms of Psychiatric Morbidity and Suicidality in Individuals Six Months After a Suicide Attempt Attending a Tertiary Care Hospital. - Subram sannapareddy,; Alekya Mudireddy, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: A high suicide rate of 12.4% was reported in India in 2022. A previous suicide attempt and the presence of psychiatric disorders are risk factors for death due to suicide. Most of the existing literature is based on cross-sectional assessments in the immediate aftermath of an attempt and not much is known about the psychiatric morbidity in these individuals afterwards. This study aimed to assess the psychiatric morbidity and suicidality in individuals 6-18 months after a suicide attempt. Methods: A hospital-based descriptive study was conducted among individuals with a history of a suicide attempt in the preceding 6-18 months. A convenient sample of 62 subjects was obtained. The presence of a psychiatric disorder and current suicidality were assessed using M.I.N.I 5.0. Hamilton Depression Rating Scale, Hamilton Anxiety Rating Scale and Global Assessment of Functioning scale were employed to assess the levels of depression, anxiety, and functioning respectively. Results: 90.3% of the individuals had at least one psychiatric disorder and 56.5% had multiple psychiatric disorders. 30.6% and 8.1% had moderate and high suicidal risk respectively. Majority of the participants had mild levels of depression and anxiety, and moderate difficulties in functioning. The presence of multiple psychiatric disorders and severity of depression emerged as significant predictors of suicidality. Conclusions: A significant proportion of individuals with a suicide attempt had psychiatric disorders, moderate to high levels of suicidality, and difficulties in functioning 6-18 months after the attempt. Regular follow-ups and interventions to reduce the risk of subsequent suicides must be ensured.